FAKTOR-FAKTOR YANG BERHUBUNGAN PERILAKU SEKS PRANIKAH DI SMA NEGRI 14 MAKASSAR - Rusli Taher; Ripka (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2022)
Objective: This study aimed to mengetahuai factors associated with premarital sexual behavior in SMA Negeri 14 Makassar. Methods: This study was an observational survey-analytic using case control design using purposive sampling and sample of 24 respondents, and using a questionnaire measuring instrument. Chi-Square test was conducted to determine the factors related to premarital sexual behavior in SMA Negeri 14 Makassar. Results: The Chi-Square test showed that there is a correlation with the level of knowledge of premarital sexual behavior with a value of p = 0.172. There is a relationship milieu with premarital sexual behavior with a value of p = 0.000. There is a relationship resources with premarital sexual behavior with a value of p = 0.626. There is a relationship of family roles with premarital sexual behavior with a value of p = 0.172. Discussion: premarital sex behavior usually associated with curiosity or adolescent curiosity about new things in life. Where knowledge of adolescents about sex before marriage is not based sexual education both from the school and from activities on adolescent reproductive health could do that. Conclusion: The results of the study conclude that the relationship between the level of knowledge, social environment, resources, and the role of families with premarital sexual behavior in SMA Negeri 14 Makassar. Suggestions in this study is expected this study as one of the contributions of scientific thought and can multiply science and reading material for the next researcher